Volume 6: Turbo Expo 2004 2004
DOI: 10.1115/gt2004-53917
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Performance of Oxidation and Creep-Resistant Stainless Steels in an Exhaust Gas Primary Surface Recuperator Application

Abstract: Recuperation increases the efficiency of a gas turbine engine by extracting heat from the exhaust gas stream and using it to pre-heat the compressor discharge air. Oxidation of the thin metal foil recuperator walls is a major concern, necessitating the use of heat-resistant alloys. Water vapor, present in the exhaust gas as a by-product of combustion, has been shown to be detrimental to the elevated temperature oxidation resistance of some ferrous alloys currently used for recuperators, e.g., Type 347 stainles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The alloy has a large variety of applications for instance in aerospace industries, chemical processing, pollution control equipment, waste‐to‐energy boilers and recuperators . Recently, alloy 625 was considered as a potential construction material for gas turbine recuperators and its oxidation behaviour in water vapour containing exhaust gases was studied during long‐term exposures in a wide temperature range .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The alloy has a large variety of applications for instance in aerospace industries, chemical processing, pollution control equipment, waste‐to‐energy boilers and recuperators . Recently, alloy 625 was considered as a potential construction material for gas turbine recuperators and its oxidation behaviour in water vapour containing exhaust gases was studied during long‐term exposures in a wide temperature range .…”
Section: Introductionmentioning
confidence: 99%
“…Refs. ) and its significance for the overall oxidation performance is well established when considering materials behaviour at temperatures around and above 900 °C . Especially from extensive studies carried out at Chalmers University of Technology (Göteborg, S) it was shown that the formation of volatile chromium species may also substantially affect materials performance at much lower temperatures around 600 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results vary from study to study, but water vapor tends to accelerate the rate of oxidation, leads to the formation of layered scales, and increases the amount of chromium required to form a protective oxide film. Work focused specifically on Fe-Cr-Ni alloys suggests that higher chromium and nickel contents (or conversely, a low iron content) increase oxidation resistance in environments containing water vapor [24][25][26][27][28][29][30][31][32][33]. Studies involving austenitic stainless steels noted that a thin chromium oxide layer is established on the sample surface during initial exposure to air containing water vapor.…”
Section: Introductionmentioning
confidence: 99%